Gambling Disorder: A Preliminary Study of the Integration of Psychology and Islam - Hidayat, Bahril; Wina Diana Sari; Iredho Fani Reza; Azhar Jaafar; Raja Syahla Medina Lailafna; Lailatul Syahrina; Alysa Rafika Putri (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, Sumatra Selatan, 2025)
Online gambling is increasingly prevalent in the digital era and impacts psychological, social, and spiritual aspects. Gambling disorder is categorized as an impulse control disorder associated with impulsivity, anxiety, depression, and cognitive biases. From an Islamic perspective, maysir is strictly prohibited because it damages reason, property, and social order, and contradicts the maqasid al-shariah. This study used descriptive qualitative methods through library research and content analysis of psychological literature and Islamic texts. The results indicate that gambling causes financial loss, family conflict, social isolation, and a decline in mental-spiritual health. Islam views the prohibition of gambling as a protective mechanism for the soul, mind, and morals. The study recommends an Islamic psychospiritual rehabilitation model that integrates Cognitive Behavioral Therapy with the practices of tazkiyah al-nafs, dhikr, and strengthening faith, as well as the importance of public policy and Islamic counseling programs in educational institutions, Islamic boarding schools, and clinical services.